Analisis Atas Efektivitas Pengelolaan Data Dan Informasi Kependudukan Pada Pemda Kabupaten/Kota Dan Instansi Terkait Lainnya - erwin antoni; silviana . (Universitas Widyatama, 2019)
Population administration is a series of activities in structuring and controlling population documents and data through population registration, civil registration, management of population administration information and utilization of its results for public services and development of other sectors. In the 2015-2019 RPJMN it is mentioned that Population and Family Planning (KKB) Development is directed at one of them: Improving the quality of population data and information as the basis for developing development policies and programs and implementing basic population services. One of the authorities of the Regency / City Government is to carry out community service activities in the area of ??Population Administration. The local government plays an important role in improving the quality of data and information on the population. This paper discusses the administration of population administration in regency/city governments and other relevant agencies. The discussion covers the background of topic selection, general description, regulation, business process on the object of research and risk analysis of the business process. Next, the objectives and types of research are discussed, the period of time, the number and competence of researchers, the methodology and procedures of the research to be conducted. The selection of key areas uses the RIS analysis method (Risk Management, Research Impacts, Significance). The results of this study are expected to provide appropriate and actionable recommendations in order to improve the quality of population data and information.